La validez de la prueba indiciaria en el proceso penal - Alvear Tobar, Estefany (2020)
Over time, Processual Law has evolved, in consequence it has appeared different classes of proof like the circumstantialevidence. Nowadays the majority doctrinal position accepts the use of it, because it says that it avoids that crimes that do not have direct proof remain unpunished. The purpose of this proof is to reach a conclusion about its validity in base of another proof, which open a gap in regard of the analysis of the judge because it does no exist direct evidence, so it is possible that the authority does not have certainty of the facts.